Pengabdian Masyarakat Berbasis Edukasi Partisipatif dalam Pencegahan Perundungan di SMP Negeri 6 Pagelaran, Kecamatan Pagelaran Cianjur Selatan (Lembaga Pengembangan Kinerja Dosen, 2025)
Bullying remains a serious issue in the education sector, particularly at the junior high school level. The lack of students’ understanding regarding forms of bullying often leads to behaviors considered jokes, such as calling peers by their parents’ names, which can cause psychological harm. This community service program aimed to raise awareness among students of SMP Negeri 6 Pagelaran about the dangers of bullying and to build a collective commitment to its prevention. The method employed was Asset-Based Community Development (ABCD) through four stages: Discovery, Dream, Design, and Destiny. The results revealed that students developed a better understanding of the definitions, forms, and impacts of bullying. Active participation through discussions, games, and reflections encouraged students to design simple preventive strategies and establish class-wide agreements. The collective commitment generated by this program demonstrated that interactive educational approaches are effective in fostering awareness, empathy, and shared responsibility to create a safe, inclusive, and bullying-free school environment.